Manipulation in the Indonesian Translation of The Secret Garden and the Translation Product Quality - Annisa Nur Atikah; Issy Yuliasri; Hendi Pratama (English Education Journal, 2024)
This study examines the manipulation of the text in Frances Hodgson Burnett's English novel